PENGARUH EFISIENSI MODAL KERJA, PERTUMBUHAN PENJUALAN DAN UKURAN PERUSAHAAN TERHADAP PROFITABILITAS PERUSAHAAN - Miswanto Miswanto; Yanuar Rifqi Abdullah; Shofia Suparti (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2017)
The purpose of this study is to examine the effect of Working Capital Efficiency, Sales Growth, and Company Size on Profitability of manufacturing companies listed in Indonesia Stock Exchange period 2012-2014. This research is expected to be useful for the company to know the policy to be taken for business continuity. Based on the results of tests on the existing hypothesis, the results of this study as follows. Working Capital Turnover (WCT) has a positive and significant effect on profitability. The growth of the Company which is proxied by sales growth has negative and insignificant effect on profitability. Firm Size's firm size has a positive and significant effect on profitability. Therefore, profitability and firm size can be used to predict profitability of manufacturing companies listed on Indonesia Stock Exchange period 2012-201. , Keywords: Profitability, working capital, company growth, and firm size